2008
DOI: 10.1186/1744-8069-4-37
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Extreme Pain Disorder M1627K Mutation in Human Nav1.7 Renders DRG Neurons Hyperexcitable

Abstract: BackgroundParoxysmal extreme pain disorder (PEPD) is an autosomal dominant painful neuropathy with many, but not all, cases linked to gain-of-function mutations in SCN9A which encodes voltage-gated sodium channel Nav1.7. Severe pain episodes and skin flushing start in infancy and are induced by perianal probing or bowl movement, and pain progresses to ocular and mandibular areas with age. Carbamazepine has been effective in relieving symptoms, while other drugs including other anti-epileptics are less effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
116
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 54 publications
8
116
0
Order By: Relevance
“…Altered expression of VGSCs that are found in primary sensory neurons, e.g. NaV1.3, NaV1.7, NaV1.8, and NaV1.9, has been shown to associate at various degrees with human neuropathies (12)(13)(14)(15)(16)(17) and animal neuropathy models (18 -21). Among the peripheral VGSC isoforms, NaV1.8 is the predominant tetrodotoxin-resistant sodium channel expressed exclusively in primary sensory neurons with particularly high levels of expression in nociceptive neurons of small-and medium-sized soma diameters (22).…”
mentioning
confidence: 99%
“…Altered expression of VGSCs that are found in primary sensory neurons, e.g. NaV1.3, NaV1.7, NaV1.8, and NaV1.9, has been shown to associate at various degrees with human neuropathies (12)(13)(14)(15)(16)(17) and animal neuropathy models (18 -21). Among the peripheral VGSC isoforms, NaV1.8 is the predominant tetrodotoxin-resistant sodium channel expressed exclusively in primary sensory neurons with particularly high levels of expression in nociceptive neurons of small-and medium-sized soma diameters (22).…”
mentioning
confidence: 99%
“…Met1627Lys mutation has been previously described in a sporadic case of paroxysmal extreme pain disorder from France [1], and then reported in an English family [2]. In both families, carbamazepine was effective with low-doses in two adult women (200 to 600 mg/d) reducing the frequency of attacks to just one a year.…”
Section: Discussionmentioning
confidence: 95%
“…The (adult) patients with the M1627K mutation were carbamazepine-responsive with 600 mg/d, whereas a dose of 400 mg/d in a two-year-old boy weighing 8 kg merely halved the frequency of the pain attacks to one every two days. A number of voltage-clamp studies have shown that the M1627K mutation has a marked effect on fast inactivation of NaV1.7 [1][2][3] and resurgent sodium currents [3]. However none of these electrophysiological studies assessed the effect of carbamazepine in the M1627K mutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The universe of painful Na-channelopathies -human disorders caused by mutations in voltage-gated sodium channels -has recently expanded in three dimensions. We now know that mutations of sodium channels cause not only rare genetic 'model disorders' such as inherited erythromelalgia and channelopathy-associated insensitivity to pain but also common painful neuropathies.The discovery of genetic variants that substantially alter an individual's perception of pain has led to a step-change in our understanding of molecular events underlying the detection and transmission of noxious stimuli by the peripheral nervous system [2]. The voltage-gated sodium ion channel Nav 1.7 is expressed selectively in sensory and autonomic neurons; inactivating mutations in SCN9A, which encodes Nav 1.7, result in congenital insensitivity to pain, whereas gain-of-function mutations in this gene produce distinct pain syndromes.…”
mentioning
confidence: 99%